Transylvanian noble residence gardens. Landscape gardens, the ’prospect" and the ’eye-catcher’ - Fekete, Albert (4D Journal of Landscape Architecture and Garden Art, 2010)
18th century Transylvanian gardens, which usually followed French design with a large pond in the middle of the garden. In the nineteenth century these gardens were transformed into landscape gardens as a sign of passive resistance to the foreign oppression represented by the Viennese Baroque. These artistic gardens, which represent a new ideology, no longer symbolize grandeur, but they are intimate retreats suitable for solitude and contemplation.